2009
DOI: 10.1021/ja809851d
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Arrays Responsive to Additives. Fluorescence Tuning

Abstract: The application of low-flux sunlight begins with the synthesis of effective antenna systems. This requires the development of dye integrates with optimized dye orientation for effective energy transfer. We here report a series of peptide-linked porphyrin arrays, denoted by Boc-(Por(Zn,S))(n)-OBu(t) (n = 2, 4, and 8), that change their dye orientation to increase fluorescence responsively to additive reagents. The B-band absorption (AB) regions of the arrays show blue shifts (dimer, 407.6 nm; tetramer, 408.2 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…37,39 The Vilsmeier formylation of tetraalkylporphyrins has been reported previously albeit in very low yields. 40,41 We also found that using the DMF-POCl 3 formylation complex at 80-90 C produces mostly decomposition products. Shortening the reaction time to 50 min gave 2 in low yield (<20%) with recovery of some unreacted 1, whilst lowering the reaction temperature below 70 C did not give any appreciable product.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…37,39 The Vilsmeier formylation of tetraalkylporphyrins has been reported previously albeit in very low yields. 40,41 We also found that using the DMF-POCl 3 formylation complex at 80-90 C produces mostly decomposition products. Shortening the reaction time to 50 min gave 2 in low yield (<20%) with recovery of some unreacted 1, whilst lowering the reaction temperature below 70 C did not give any appreciable product.…”
Section: Resultsmentioning
confidence: 68%
“…37 Usage of such harsh conditions decreases the yield of the free-base tetraalkylporphyrin. 41 As a result, we have utilized here the milder procedure described by Ponomarev and Maravin. 42 A cooled solution of porphyrin 2 dissolved in a small amount of POCl 3 is treated with water (10% by volume).…”
Section: Resultsmentioning
confidence: 99%
“…6). 52 The Soret band of the arrays exhibited blue shifts in organic solvents compared to that of the monomer, and the fluorescence yield of the arrays decreased with increasing unit numbers. By balancing the van der Waals interactions, p-p interactions, ligand coordination, and formation of peptide secondary structure, appended porphyrins in the array maintain their mutual orientation.…”
Section: Photoluminescencementioning
confidence: 96%
“…46,47 The Q-bands were also observed to be redshifted to 558 and 596 nm, respectively, suggesting that the porphyrin molecule was in a face-to-face-packing in TThPP film. 48 TThP showed two obvious fluorescence peaks at 661 and 720 nm, respectively, whereas the TThPP film red-shifted to 668 and 725 nm. The intensity ratio of the peak at 668 to 725 nm of the TThPP film increased as compared to that of TThP, suggesting the increase of the planarity of porphyrins in the polymer.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 97%